Respuesta :

Answer:

  1. f(x) = x^3 -4x
  2. f(x) = -2x^3 +8x

Step-by-step explanation:

The zeros are at -2, 0, and +2, so the function will be of the form ...

  f(x) = k·(x +2)(x)(x -2) . . . . . for some vertical expansion factor k

You recognize that (x+2)(x-2) is the factoring of the difference of squares, so ...

  f(x) = k·x·(x^2 -4)

If we let x=1, we get

  f(1) = k·(1)(1 -4) = -3k

For the first graph, it looks like we have ...

  f(1) = -3 = -3k . . . . so, k = 1

For the second graph, it looks like we have ...

  f(1) = 6 = -3k . . . . so, k = -2

_____

In standard form, the first graph is described by ...

  f(x) = 1·x·(x^2 -4) = x^3 -4x

The second graph is described by ...

  f(x) = -2x·(x^2 -4) = -2x^3 +8x

Ver imagen sqdancefan